Assessing the world's forest resources. - SINGH, K.D. (1995)
Presents an overview of the FAO forest resources assessment, which describes the state of forests in 1990 and changes during the 1980s. The assessment looked at forest area status, change in forest area, long term trends, volume and biomass, trends in wood consumption, and global climate change.